Forensic tanatology: biological and legal aspects - Arsenio Sales-Peres; Ricardo Henrique Alves d Silva; César Lopes-Júnior; Suzana Papile Maciel Carvalho (Universidade Estadual de Campinas, 2016)
The forensic tanatology is a term which remits to a Greek origin: thanatos meaning death and logy meaning study. This way the discussed subject is wide however it refers only to human death. The purpose of this work is through a literature review give an actualization dates to law professionals, as well as to those who work in peritial activity in Medicine and Dentistry, searching to approach questions referred to death diagnostic and its certification, its law aspects and details referred to peritial tests in Tanatology.